Characterization of collagen from emu (Dromaius novaehollandiae) skins - Nagai, Takeshi (J Food Sci Technol, 2014)
Collagen from emu skins as a by-product was prepared. The skins were hardly solubilized in acetic acid, however were successfully solubilized on digestion with 10 % pepsin (w/w) for 4 days. The yield of pepsin-solubilized collagen (PSC) was about 27.3 %, on a raw weight basis. By SDS-PAGE and CM-Toyopearl 650 M column chromatography, the presence of a fourth subunit that was previously designated α4 was confirmed. The denaturation temperature of the PSC was 31.5 °C, about 6–7 °C lower than that from the porcine skins. ATR-FTIR analysis indicated that the helical arrangements of the PSC from emu skins existed and its structures of PSC were changed slightly due to the loss of N- and C-terminus domains in similar to that from the porcine skins. That is, the PSC from emu skins did not possess telopeptide chains as major portion of antigenic sites in collagen. The present study indicates that a large quantity of emu skins as by-products have potential as a good alternative source of high-quality collagen for industrial purposes in the foods, cosmetics, and pharmaceutical and biomedical fields.